TINDAK PIDANA PENYEROBATAN TANAH DALAM PERSPEKTIF HUKUM PIDANA - Jaminuddin Marbun; Raja Kenasihen Ginting; Anggara Zuhri Harahap (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
Land grabbing is an act of taking rights or assets arbitrarily or by ignoring the laws and regulations, such as occupying land or other people's houses that are not their rights. Illegal land grabbing is an act that is against the law, which can be classified as a crime. The formulation of the problem studied in this thesis is how to regulate the crime of land grabbing, how are the factors causing the crime of land grabbing, how to enforce the law against the crime of land grabbing. The research method used in this research is using normative juridical research sourced from library research using secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of the study show that the regulation of criminal acts of land grabbing is regulated in several provisions for the regulation of criminal acts of land grabbing regulated in several statutory provisions, including Law Number 51 PRP of 1960 which states that land use without a rightful permit or legal proxy is an act that is illegal. prohibited and threatened with criminal penalties (Article 2 and Article 6) and regulated in the Criminal Code in several articles, namely Article 167, Article 242, Article 263, Article 264, Article 266, Article 274, and Article 385 of the Criminal Code. The factors causing the crime of land grabbing are the land owner's indifference to the assets he owns, the victim's ignorance about the ownership of the land having been sold or given to someone else by the victim's parents, the high price of land which causes people to start looking for their land and also resulting in difficulty in obtaining land for cultivation, the sale of parents' land first using a belief system so that there is no evidence related to the transfer of land rights. Law enforcement against land grabbing is subject to Article 385 of the Criminal Code which is the only article directly related to land grabbing and is categorized as a criminal offense. Especially in Article 385 paragraph (1) of the Criminal Code which reads: